Educational Game "Sianting" to Improve Literacy and Anti-Bullying Education Using Problem-Solving Approach - Kirom, Sabitul; Rosyida, Desy Anindia (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The implementation of this research is due to the ineffective literacy learning and anti-bullying education in schools. Acts of bullying experienced by students at school still occur. The research objectives: (1) develop an educational game 'Sianting' with a problem-solving approach that integrates literacy learning with anti-bullying education; (2) test the feasibility of the 'Sianting' educational game. This research was conducted using the ADDIE model R&D method. Data collection techniques used were observation, interviews, documentation, and tests. The 'Sianting' game media was tested through expert and field tests. The results showed that the 'Sianting' game was declared valid based on expert and user validation. 'Sianting" game is effectively applied in literacy learning and anti-bullying education at school. The practicality of the 'Sianting' game is very good. The results of material expert validation get a percentage value of 95%, media experts get a percentage of 93.75%, and users get a percentage value of 92.5%, so it is 'very valid.' The results of limited trials in small groups get a percentage value of 89.37%, and extensive trials in large groups get a percentage value of 91.47%. The average pretest results get a value of 69, and the average post-test gets a value of 86, showing an increase in the average value obtained by students after using the 'Sianting' educational game media. Thus, the 'Sianting' game is valid, practical, and effective in improving students' literacy skills and anti-bullying educational understanding of media.